Comparison of Antimicrobial and Membrane Stabilizing Properties of Leaf and Stem Extracts of Derris scandens (Roxb.) Benth. (Family: Fabaceae) - Shahriar, Saimon; Jaman, Asif Uj; Saha, Samir; Islam, Md Sabbarul; Islam, Md Rafiqul; Saha, Biprojit; Sikder, Md Al Amin; Rashid, Mohammad A (Bangladesh Pharmaceutical Journal, 2023)
Derris scandens (Roxb.) Benth. (Family: Fabaceae), a recognized medicinal plant colloquially known as ‘Kalilata’ in Bangladesh, has been traditionally used as analgesic in Thailand. This study was intended to evaluate and compare the antimicrobial and membrane stabilizing potentials among the methanol extracts of D. scandens leaf and stem, and their fractionates. The stem and leaves of the plant were extracted by methanol separately and fractioned into aqueous, dicholoromethane (DCM), ethyl acetate and n-hexane soluble fractions. They were tested for antimicrobial activity by using the agar-well diffusion method where ciprofloxacin and fluconazole were used as references. The highest antimicrobial activity was observed against a Gram-negative bacteria (Escherichia coli) by the DCM soluble fraction of the leaf and stem extracts with 20 mm and 15 mm zones of inhibition, respectively. The n-hexane soluble fraction of methanol extract of stem revealed weak to moderate antimicrobial activity against Gram-positive bacteria. The ethyl acetate soluble fractionates of methanol extracts of leaf and stem showed similar antifungal property against Saccharomyces cerevisiae with a zone of inhibition of 12 mm. The membrane stabilizing potential of the extractives was estimated based on the prevention of hemolysis of RBC prompted by hypotonic solution as well as heat. The n-hexane and DCM soluble fractions of both extracts showed around 75% inhibition of hypotonic solution- and heatinduced hemolysis. All in all, the extracts and several fractionates showed moderate antimicrobial and membrane stabilizing properties and further investigations are warranted to find out active phytoconstituents responsible for these properties. Bangladesh Pharmaceutical Journal 26(1): 67-72, 2023 (January)